KOMUNIKASI MATEMATIS SISWA DALAM MENYELESAIKAN SOAL OPENENDED - Lilik Fauziah; Sudirman Sudirman; Abadyo Abadyo (FMIPA UNIVERSITAS NEGERI MALANG, 2020)
Mathematical communication is the ability to convey mathematical ideas both verbally (orally) and in writing (in writing). Mathematical communication is a standard process that should be one of the focuses of teachers' attention in mathematics learning. One way to develop students' mathematical communication is to train students to work on open-ended questions and carry out activities related to these abilities. Open-ended questions give students the opportunity to explore their ideas and thoughts in solving a problem. This study aims to describe students' mathematical communication in solving open-ended questions on Statistics material. This research uses QCAI mathematical communication criteria in the QUASAR Project and relates it to the problem solving theory according to Polya. The data were obtained through students' answers after giving open-ended questions to students. The research subjects were 3 students who were selected from groups of high, medium, and low cognitive levels. S1 gives a response by writing 15 kinds of correct answers, S2 and S3 only write down only one kind of correct answer. Subjects have various mathematical communication and their own ways of how to communicate their answers effectively to others and provide strong arguments that support their answers both orally and in writing. Keywords: matematical communication, open-ended, Polya